Example of C-rigid polytopes which are not B-rigid - Choi, Suyoung; Park, Kyoungsuk (Mathematica Slovaca, 2019)
A simple polytope P is said to be B-rigid if its combinatorial structure is characterized by its Tor-Algebra, and is said to be C-rigid if its combinatorial structure is characterized by the cohomology ring of a quasitoric manifold over P. It is known that a B-rigid simple polytope is C-rigid. In this paper, we show that the B-rigidity is not equivalent to the C-rigidity.
Keywords: B-rigid; cohomologically rigid; Peterson graph; quasitoric manifold; simple polytope